2003
DOI: 10.1088/0953-8984/15/26/311
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the spin glass transition in a low U doped YRu2Si2sample

Abstract: We have made extensive studies of a dilute U doped YRu2Si2 alloy using several experimental techniques such as ac and dc magnetic susceptibility, dc resistivity and microstructural investigations. The real part of the ac susceptibility shows a maximum at around 6.75 K for f = 7 Hz. With increasing frequency, the temperature of this maximum increases while, at the same time, the magnitude of the maximum decreases, which is a typical spin glass behaviour. The magnitude of the imaginary part shows frequency-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This last equation implies a linear dependence of T f with 1/ln(u 0 /u) and has been often used to describe the slowing down of the relaxation found in spin glasses [19], with T 0 having the same order of magnitude of T f . The Vogel-Fulcher plot for U 3 Fe 4þx Al 12Àx is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…This last equation implies a linear dependence of T f with 1/ln(u 0 /u) and has been often used to describe the slowing down of the relaxation found in spin glasses [19], with T 0 having the same order of magnitude of T f . The Vogel-Fulcher plot for U 3 Fe 4þx Al 12Àx is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The existence of two crystalline phases even in such low concentrated alloy was revealed. It was shown that only c = 0.035 of U was in the solid solution in this investigated sample [12].…”
Section: Introductionmentioning
confidence: 66%
“…Under a reasonable assumption that the density of electronic states g does not vary significantly for the above mentioned compounds, we conclude that hybridization in the U x Y 1−x Ru 2 Si 2 alloys is weak. This could explain why Kondo interaction is not observed for the lower concentrations of U [8][9][10][11][12][13]. In addition, the influence of the secondary phase, which exists also even for the lowest concentrations investigated [12] on the transport properties, is probably more significant for the low U concentrations.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further point pertaining to the presented work here is the fact that the spin glass GS can be formed with very small concentration of a Kondo ion in some metal matrix. For example, only less than 0.1 at.% of U forms the spin glass GS in Yru 2 Si 2 [10,11]. This spin glass shows ferromagnetic like behavior.…”
mentioning
confidence: 99%